Fabrication Of Ti-40Nb-10HA Composite And Ti-40Nb Alloy With Surface Nanotubes For Implant Application - Chu, Chia Shin (Universiti Sains Malaysia, 2018)
The criteria of today’s biomaterials has included both physical properties and its ability to promote growth of body tissue. In today’s technology, there are two methods to improve bioactivity of the biomaterials are by adding bioactive materials such as hydroxyapatite (HA) and surface modification of the materials. Hence, the mechanical properties and bioactivity of Ti-40Nb-10HA composite was studied and the investigation of the feasibility of forming nanotubes on Ti-40Nb alloy was also conducted. Ti-40Nb-10HA and Ti-40Nb was fabricated by powder metallurgy method with the compaction pressure of 500 MPa. Ti-40Nb-10HA was sintered at variation of temperature (900°C –1300 °C). Mechanical testings’ results show that the densification occurs when the sintering temperature increases. The relative density of the sintered composite increases as sintering temperature increases from 91.54% to 97.09%. The corrosion rates of the sintered Ti-40Nb-10HA composite is within the range of 0.0348 to 0.1494 mm/year. The modulus of the composite increase as the sintering temperature increase from 1000 °C to 1300 °C (17.6 GPa to 20.03 GPa) which is comparable with the modulus of human bone which is 18GPa. The Ti-40Nb-10HA composite sintered at 1100°C to 1300 °C show increasing micro hardness (112.46 HV to 183.85 HV) and compressive strength (159 MPa to 193.33 MPa). In-vivo evaluation in HBSS for 7 days, nucleation and growth of apatite increases as the sintering temperature increases from 1000°C to 1200°C while the surface modification of Ti-Nb (sintered at 1200°C) exhibited formation of oxide nanotube with reducing diameter from 70 nm to 50 nm when volume percentage of NH4F in electrolyte increased from 0.5 vol% to 0.7 vol%.